2019
DOI: 10.3389/fimmu.2019.02422
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Strategy to Improve the Development of a Coral Antivenom Against Micrurus spp.

Abstract: Accidents involving Micrurus snakes are not the most common ones but are noteworthy due to their severity. Victims envenomed by Micrurus snakes are at high risk of death and therefore must be treated with coral antivenom. In Brazil, the immunization mixture used to fabricate coral antivenom contains Micrurus frontalis and Micrurus corallinus venoms, which are difficult to be obtained in adequate amounts. Different approaches to solve the venom limitation problem have been attempted, including the use of synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…A closer inspection of other predicted epitopes revealed that some short motifs within them are indeed part of other already validated epitopes. For instance, it is interesting to find that motif ATCP, present in the predicted epitopes ATCPKPTNVRETI and AATCPKVK that cover Dendroaspis species and which have been predicted through 3D features, has been found in validated 3FTXs epitopes from the Asian Bungarus multicinctus and the American Micrurus corallinus [36,37]. Nonetheless, a limitation of the study is that most of the epitope sequences identified were predicted and yet await experimental validation of their biological function.…”
Section: Discussionmentioning
confidence: 98%
“…A closer inspection of other predicted epitopes revealed that some short motifs within them are indeed part of other already validated epitopes. For instance, it is interesting to find that motif ATCP, present in the predicted epitopes ATCPKPTNVRETI and AATCPKVK that cover Dendroaspis species and which have been predicted through 3D features, has been found in validated 3FTXs epitopes from the Asian Bungarus multicinctus and the American Micrurus corallinus [36,37]. Nonetheless, a limitation of the study is that most of the epitope sequences identified were predicted and yet await experimental validation of their biological function.…”
Section: Discussionmentioning
confidence: 98%
“…They are considered ideal organisms for ecological, evolutionary, pharmacological, physiological, phylogenetic, and proteomic studies [ 29 ]. Their ability to produce small quantities of venoms has limited the manufacturing of antivenoms as well as structural, functional, and immunological research [ 35 ]. The first integrative venom proteomics using coral snake was developed in 2008 [ 36 ], but most of the quantitative estimation of proteome compositions were published in the last 10 years [ 27 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Efforts to develop a combined antivenin to Micrurus species are underway in South America, where Micrurus species diversity is greater. 38,39 As NACSA is prone to periods of shortages lasting several years, a combined Micrurus antivenin might be investigated for use in M fulvius envenomations in the future. Research is also underway to develop a more efficient method of producing antivenin for the South American species Micrurus corallinus using genetic immunization with a synthetic multiepitope gene followed by booster doses with recombinant protein.…”
Section: Discussionmentioning
confidence: 99%